Principle of a common climate or theory of collective goods (collective action on climate). Mancur Olson, Olivier Goddard." - Diffalah, Khaouni (Journal of Social Sciences and Humanities, 2019)
Many issues have been raised nationally and internationally, concerning climate change and environmental pollution because of GHG emissions. For economic reasons and societal wellbeing, the use of fossil and fossil fuels becomes a categorical imperative. But the consequences were highly influential on the ecosystem and biodiversity. Many plants and animals have disappeared, the appearance of diseases that threaten the lives of human beings and decreases life expectancy. Philosophers, economists, lawyers, politicians, unions and associations, everyone becomes united because this climate good is common and this collective good is threatened by negative externalities caused by man and his greed. What makes us think, that each individual is responsible for his behavior in terms of excessive exploitation of fossil and fossil energies. So we are motivated to contribute to compensation by paying a tax to reduce its nuisances, for example the profit of a polluting company, and the "net collective product". The tax is suggested as a way to eliminate a market failure, or what is considered today as polluter pays. Will these solicited solutions be sufficient to preserve in the long term the common good of all? The analysis of this problematic situation, concerning the climate as a collective good, requires, in my opinion, to refer to studies made by economists and philosophers like Moncur Olson, and Olivier Godard